What Determines Foreign Direct Investment in Muslim Countries? - Azzaki, Muhammad Adnan; Qizam, Ibnu; Qoyum, Abdul (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
This study examines the influence of institutional quality, green economy policies, and financial development on Foreign Direct Investment (FDI) in Muslim countries. It employed panel data from 2010 to 2020 and is analyzed using the Dynamic Panel Model with the Generalized Method of Moments (GMM), which allows for handling endogeneity problems that often arise in panel data analysis. Statistical testing revealed that most institutional quality indicators, such as Political Stability, Government Effectiveness, Regulatory Quality, and Rule of Law, significantly and positively impact foreign direct investment. Additionally, the green economy, represented by natural resources, human capital, and the overall regulatory environment, also exerts a significant positive effect on foreign direct investment. Similar outcomes were observed in the financial sector's development, which significantly and positively reinforced the relationship between institutional quality and the green economy on foreign direct investment in Muslim countries. These results suggest a positive trajectory for resource management potential that can enhance the investment climate in Muslim countries. The findings offer valuable insights for policymakers in formulating effective strategies to boost capital inflows in Muslim countries. Policymakers are advised to consistently monitor both institutional quality and green economy indicators to discern investor preferences for foreign direct investment inflows.==============================================================================================================ABSTRAK – Determinan Apa yang Mempengaruhi Investasi Asing Langsung di Negara-negara Muslim? Paper ini menguji pengaruh kualitas kelembagaan, kebijakan ekonomi hijau, dan pembangunan keuangan terhadap Investasi Asing Langsung (FDI) di negara-negara Muslim. Studi ini menggunakan data panel tahun 2010 hingga 2020 yang dianalisis dengan Model Panel Dinamis dengan Generalized Method of Moments (GMM) yang memungkinkan penanganan masalah endogenitas yang sering muncul dalam analisis data panel. Hasil pengujian statistik menunjukkan bahwa sebagian besar indikator kualitas kelembagaan yang diwakili oleh Stabilitas Politik, Efektivitas Pemerintah, Kualitas Peraturan, dan Supremasi Hukum berpengaruh positif signifikan terhadap penanaman modal asing langsung. Selain itu, ekonomi hijau, yang tercermin pada sumber daya alam, sumber daya manusia, dan peraturan lingkungan secara keseluruhan mempunyai dampak positif yang signifikan terhadap investasi asing langsung. Hasil serupa juga diperoleh pada pengembangan sektor keuangan yang mampu memperkuat hubungan kualitas institusi dan ekonomi hijau terhadap investasi asing langsung di negara-negara Muslim secara positif dan signifikan. Temuan ini menunjukkan tren positif mengenai potensi pengelolaan sumber daya yang dapat menciptakan manfaat bagi iklim investasi di negara-negara Muslim. Temuan-temuan ini juga mempunyai implikasi berharga bagi para pembuat kebijakan dalam merancang strategi efektif untuk meningkatkan aliran modal di negara-negara Muslim. Mereka disarankan untuk terus memantau kualitas kelembagaan dan indikator ekonomi hijau untuk mengidentifikasi preferensi investor terhadap arus masuk investasi asing langsung.